COMPARATIVE STUDIES ON THE EFFECTS OF LA SOTA AND KOMAROV VACCINE ANTIBODIES ON ORGAN DISTRIBUTION, PERSISTENCE AND SHEDDING OF KUDU 113 VIRUS IN CHICKENS - E. C. Okwor; D. C. Eze; G.O. N. Echeonwu; J. O. Ibu; P. C. Eze; J. O. A. Okoye (Journal of Animal and Plant Sciences, 2016)
Vaccines derived from the lentogenic and mesogenic strains are used for the protection of clinical ND in chickens. No information is available on the protection offered by these vaccines against virus replication and shedding in Nigeria. This study compared the abilities of La Sota and Komarov vaccines to protect chickens against replication and shedding in chickens challenged with the velogenic Kudu 113 virus. Five hundred and fifty day old chicks were assigned into four groups; unvaccinated and unchallenged (G1), unvaccinated and challenged (G2) La Sota vaccinated and challenged (G3) and Komarov vaccinated and challenged (G4). Batches of birds in G2, G3 and G4 were taken at specified intervals for challenge with Kudu 113. Virus distribution and persistence in organs and shedding in the faeces of the infected birds were assessed. Both vaccines did not prevent viral replication and shedding but significantly reduced the distribution and shedding of Kudu 113. Komarov vaccine showed higher reduction of viral replication and shedding when compared with La Sota. Peak distribution and shedding in both cases were seen between days 4 and 7 PC and virus persisted in the faeces of infected chickens for a maximum of 14 days in G4 and 21 days in G3.
Keywords: La Sota; Komarov; Kudu 113; distribution; persistence; shedding